ВИКОРИСТАННЯ НАТУРАЛЬНИХ ШКІР У ВЗУТТЄВОМУ ВИРОБНИЦТВІ - DANYLKOVYCH Аnatolii; NAUMENKO, Bohdan (Herald of Khmelnytskyi National University. Technical sciences, 2022)
In the work, the formation of leather material from semi-finished cattle was carried out – medium chrome-tanned beef at the stage of filling and fattening after it is planed to thickness 0,9–1,1 mm. In this case, the product of the interaction of 2-naphtholsulfonic acid with dioxydiphenylsulfone was used – BNS synthetic tanner (ТУ 17-06-165-89), mimosa extract with a tannin content of 79.0% and an emulsion of a fattening preparation Fosfol L-1301 by company «Cromogenia Units, S.A.» (Spain). Preliminary greasing of the semi-finished product and final fixation of reagents diffused into the structure of the semi-finished product with alumokalium alum gives the leather material a complex of hygienic, physical-mechanical and technological characteristics that meet the requirements for materials for sewing products. The resulting leather material exceeds industrial samples by 13.6% and 11.0%, respectively, in terms of hygroscopicity and vapor permeability. Compared to natural leather, synthetic leather is characterized by significantly lower hygienic properties, and in terms of specific surface area and sorption capacity, they are inferior to natural leather materials by at least 32.0 and 17.0 times, respectively. Accordingly, their vapor permeability and hygroscopicity are 7.0–8.0 and 5.5–6.0 times lower than natural leather. At the same time, to a greater extent, this also applies to a complex of physical and mechanical indicators, including increased defectability and reduced formability during the operation of footwear products. At the same time, their initial aesthetics are relatively quickly lost. The natural leather material obtained by the developed technology can be considered promising due to its advantages compared to synthetic leathers and compliance (ДСТУ 2726-94) for the production of high-quality shoe uppers.